Coupling Coordination Relationships Between Ecosystems and Economic Development in Qinghai and Tibet - Jie Wang; Shaohong Wu; Lulu Liu; Rui Yan; Shuang Zhou (Land)
The coordinated development of ecological protection and socioeconomics in the Tibetan Plateau is of great significance. This study examines the coupling coordination of urban ecosystems and economic development across 15 municipal administrative units in Qinghai Province and the Tibet Autonomous Region, the core areas of the Tibetan Plateau. The findings reveal that a larger proportion of the Qinghai and Tibet ecosystems are classified above the medium vulnerability level, primarily due to inherent natural geographic conditions. Additionally, the area of the two provinces and regions below the medium development level is larger, which is mainly influenced by indicators of economic strength and industrial structure. The degree of coupling coordination between the ecosystem and economic system in Qinghai and Tibet is predominantly driven by economic factors. Given the existing natural environmental conditions, the eastern regions of Qinghai and Tibet still possess certain development potential, while the economic development in the western areas is somewhat constrained by the natural environment. Based on this, further policy recommendations have been proposed to adjust and upgrade the industrial structure, aligning ecological protection with economic development in the Qinghai–Tibet Plateau. These recommendations aim to facilitate the formulation of strategies and policies for sustainable urban construction and social development in such high-ecological-value regions as the Tibetan Plateau.